The design of energy communities: optimising environment, time and place - Chiara Scanagatta; Massimiliano Condotta (Techne, 2025)
The installation of systems from renewables leads to the modification of communities’ proximity spaces, with irreversible alterations of the natural and man-made landscape. Hence the need to develop strategies to integrate these systems into the environment, preserving the value of places according to their peculiarities and characteristics. The PANORAMA project, with its multi-criteria tool integrating different aspects (potential, cost and environmental ones), promotes the activation of energy communities that benefit from solutions designed according to their specific features. The paper focuses on the aspect of environmental integration, illustrating the strategy adopted to analytically analyse and evaluate this factor, which is by nature hard to quantify.